Peran Ilmu Sosial dalam Membangun Narasi Moderasi Islam di Tengah Polarisasi Sosial - Muhammad Khairul Amri; Nikeng Putra Jaya (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
This article examines the role of social sciences in constructing the narrative of Islamic moderation amid the rising trend of social polarization in contemporary society. Polarization, triggered by political dynamics, identity conflicts, and the rapid growth of digital media, has led to social fragmentation that threatens communal cohesion. In this context, social sciences play a significant role as analytical tools to understand the dynamics of conflict, identity construction, and power relations underlying such tensions. Employing a qualitative approach through library research, this study explores recent literature on Islamic moderation and social sciences. The findings reveal that Islamic moderation rooted in the values of tawassuth (middle path), tasamuh (tolerance), i’tidal (justice), and musawah (equality) can be enriched through theoretical frameworks from the social sciences, making it more relevant in addressing contemporary issues. The integration of both perspectives allows Islamic moderation to be understood not merely as a normative slogan, but as a social praxis that strengthens inclusivity, tolerance, and justice within the public sphere. This study underscores the importance of an interdisciplinary approach to reduce social polarization and to consolidate Islamic moderation as a foundation for peaceful religious and national life.